2010
DOI: 10.1248/cpb.58.1474
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Pharmacodynamics of Exenatide-Loaded Poly(DL-lactic-co-glycolic acid) Microspheres

Abstract: ExperimentalMaterials Exenatide was synthesized in our laboratory by Peptide Synthesizer (PS3 Model, Protein Technologies Inc., U.S.A.) using the FMOC solid-phase peptide synthesis approach, and purified by reverse phase (RP)-HPLC to Ͼ95% purity. PLGA and poly lactic acid (PLA) were purchased from Birmingham Polymers (Birmingham, AL, U.S.A.). The micro-bicinchoninic acid (BCA) Assay Kit was supplied by Pierce. Polyvinyl alcohol (PVA) and STZ were purchased from Sigma. All other chemicals were of analytical gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…[11] Analysis of GLP-1 using 2D-NMR revealed that the first seven amino acid residues (7-13)a tt he N-terminusf orm ar andom coil structure,w hich is thought to be responsible for interactions with the main bindingp ortion of the GLP-1R ( Figure 2). [12] This is followed by ah elical region (14)(15)(16)(17)(18)(19)(20), al inker region (21)(22)(23) and as econd helical region (24-35) ( Figure 2). [12] Alanine scanningo fe ach GLP-1 residue further revealed that residues 7, 10, 12, 13, 15, 28 and 29 ( Figure 2) are important for binding to, and activation of the GLP-1R, with mutations at these positions reducing GLP-1Ra ffinity by 132-425-fold and potency by 12-3900-fold.…”
Section: Structure-activity Relationships For Glp-1mentioning
confidence: 97%
See 1 more Smart Citation
“…[11] Analysis of GLP-1 using 2D-NMR revealed that the first seven amino acid residues (7-13)a tt he N-terminusf orm ar andom coil structure,w hich is thought to be responsible for interactions with the main bindingp ortion of the GLP-1R ( Figure 2). [12] This is followed by ah elical region (14)(15)(16)(17)(18)(19)(20), al inker region (21)(22)(23) and as econd helical region (24-35) ( Figure 2). [12] Alanine scanningo fe ach GLP-1 residue further revealed that residues 7, 10, 12, 13, 15, 28 and 29 ( Figure 2) are important for binding to, and activation of the GLP-1R, with mutations at these positions reducing GLP-1Ra ffinity by 132-425-fold and potency by 12-3900-fold.…”
Section: Structure-activity Relationships For Glp-1mentioning
confidence: 97%
“…In this formulation, the exendin‐4 peptide is noncovalently entrapped within a biodegradable poly( d,l ‐lactide‐co‐glycolide) (PLG) polymer to form 60 μm microspheres . This results in slow release of exendin‐4 from the polymeric matrix by diffusion and hydrolysis of the microspheres, prolonging its half‐life to 5–6 days in humans, which enables more convenient once‐weekly subcutaneous injection and potentially once‐monthly dosing in the future . Despite these advantages, PLG depot formulations can display irregular drug release and instability of their peptide cargos following hydration and administration, which may have adverse clinical outcomes (e.g., the potential for nausea and vomiting due to an initial burst release, followed by a subsequent “lag‐phase”, which may decrease efficacy) .…”
Section: Strategies Used To Extend the Biological Half‐life Of Glp‐1mentioning
confidence: 99%
“…Literature unfolds various types of traditional liposomes, such as uni-lamellar (ULV) or multi-lamellar vesicular systems (MLV) (Ye et al, 2000;Karathanasis et al, 2006). Drugs/actives like cytotoxic, antidiabetics, anti-cancerous, proteinaceous and genetic material have been encapsulated in liposomal systems and it has been (Liu et al, 2010;Ryan et al, 2013;Qi et al, 2013;Xuan et al, 2013) …”
Section: Liposomesmentioning
confidence: 99%
“…The conjugation of long-chain palmitic acid (PAA, C16 to GLP-1 increased the in vivo duration of GLP-1 substantially (10). The encapsulation of another GLP-1 analog, exendin-4 from the lizard salivary gland peptide also showed sustained circulation of the peptide in the body (11). However, it may be necessary to design the long-acting technology for a GLP-1 analog for the effective delivery of this important therapeutic peptide in order to improve the patient compliance significantly.…”
Section: Introductionmentioning
confidence: 99%